2021
DOI: 10.31436/ijohs.v2i2.98
|View full text |Cite
|
Sign up to set email alerts
|

Resin Infiltration Technique as Minimal Invasive Approach Towards Mild to Moderate Dental Fluorosis in an Adolescent: a Case Report

Abstract: Dental fluorosis can be defined as a developmental condition that affects dental hard tissue, mainly enamel characterised with white or yellowish lesions due to excessive fluoride exposure. Fluorosis can have a major impact on the appearance, structure and shape of the tooth which posed a significant aesthetic concern to individuals having this condition. There are several treatments recommended in treating dental fluorosis depending on the severity of the disease itself ranging from tooth bleaching to prosthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Conditions like dental fluorosis are known to affect esthetics of teeth. It has an esthetic concern to many people particularly in the anterior region where it is more visible to others [3]. Many researchers reported that even the mild forms of fluorosis can cause deviations in the esthetic appearance of teeth [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions like dental fluorosis are known to affect esthetics of teeth. It has an esthetic concern to many people particularly in the anterior region where it is more visible to others [3]. Many researchers reported that even the mild forms of fluorosis can cause deviations in the esthetic appearance of teeth [1].…”
Section: Discussionmentioning
confidence: 99%
“…Dental fluorosis is intrinsic tooth discoloration which is caused by high fluoride absorption (>0.05 mg/kg/BW/day) during tooth development in the maturation stage of amelogenesis. Accidental ingestion of fluoride-containing dental products and >1 ppm of fluoride in drinking water are considered possible risk factors for the development of fluorosis [2], [3]. Thus with the worldwide decline of caries, the prevalence of dental fluorosis has increased in the last two decades [4].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray with arrows showing skeletal fluorosis evidenced by the diffuse bone condensation and interosseous membrane calcification of the forearm ( F ) and leg ( G ). Reprinted from ( B )—[ 127 ], ( D )—[ 128 ], ( E , F )—[ 129 ], ( G )—[ 126 ].…”
Section: Fluorinementioning
confidence: 99%